ICT and Socio-Economic Exclusion - John P. Haisken-DeNew; Conchita D'Ambrosio (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2003)
Using an innovative dataset for ICT use for five countries in Europe,we examine the impact and association of ICT on socio-economic exclusion.Using OLS regression we find significant wage premiums for PC and internet usage at the workplace.Following Dinardo/Fortin/Lemieux (1997),we examine the impact of ICT on the distribution of wages.We find that the risk of economic exclusion increases markedly for those not having ICT at the workplace,with the largest effects being found in Britain.To examine the impact of ICT on social exclusion,we create a multi-dimensional index of social exclusion,and also following DFL97,examine the change in the distribution of the exclusion index.Not being able to afford or knowing how to operate a home PC in Britain and Israel is associated with a large increase in the risk of social exclusion.
Keywords: I31; J31; I32; 330; Exclusion; Wage Differentials; Training; Lohnstruktur; Computergestütztes Verfahren; Informationstechnik; Internet; Soziale Isolation; Schätzung; Großbritannien; Italien; Deutschland; Norwegen; Israel